Development and Tests of the Water Cooling System Dedicated to Photovoltaic Panels - Krzysztof Sornek; Wojciech Goryl; Rafał Figaj; Gabriela Dąbrowska; Joanna Brezdeń (Energies, 2022)
Among all the energy production technologies based on renewables, the photovoltaic panels are the ones with the highest rate of development and applications worldwide. In this context, significant efforts are put into research on innovative materials in order to improve the performance of photovoltaic cells. Nevertheless, possibilities available to enhance the energy yield of existing technologies also exist and are explored, such as the cooling of photovoltaic modules. This approach can decrease the mean operation temperature of photovoltaic cells, leading to an increase in efficiency and energy produced. In the present paper, this method is investigated by developing and testing a dedicated water cooling system for photovoltaic panels. In order to investigate the performance of the cooling system, two market-available monocrystalline photovoltaic panels with a power of 50 and 310 Wp were tested under laboratory and real operation conditions, respectively. Based on the results obtained under laboratory conditions, the most promising variant of the cooling system was selected and assessed under real operation conditions. For this system, the maximum temperature of the water-cooled 310 Wp panel was lower by approx. 24 K compared to an uncooled panel, as pointed out by a measurement performed during a typical sunny day when solar irradiation was approximately 850 W/m2. This improvement of the cell temperature led to a 10% increase in power generated by the water-cooled photovoltaic panel compared to the uncooled one. The economic analysis revealed that the estimated simply payback time for installing the cooling system in typical domestic photovoltaic installations can be less than 10 years, while from the point of view of net present value, the introduction of the water cooling system can be a profitable option for a 10-year period when a discount rate of 5% is considered.